Human relations practices in the public sector: a case study of national disaster management organization of Ghana. - Sulemana, Sumaya (KNUST, 2025)
This Thesis Is Submitted In Partial Fulfillment Of A Requirement For The Award Of A Degree In Master Of Public Administration (MPA).